Epidemiological characteristics of high-risk population for cardiovascular disease of Shanghai residents - WANG Yuzhuo; ZHENG Yang; WANG Yingquan; WU Cui; GU Haiyan; ZHANG Yiying; XU Yan; WANG Sen; ZHANG Xin; JIANG Yu; ZHAO Jia; SHI Yan (Shanghai yufang yixue, 2024)
ObjectiveTo investigate the high-risk detection rate and aggregation of cardiovascular diseases（CVD） in 8 districts of Shanghai and influencing factors， and to provide scientific references for prevention and control of CVD.MethodsBased on the Cardiovascular Disease Screening and Management Program in Shanghai from 2016 to 2021， 104 685 participants aged 35 to 75 in 8 districts of Shanghai were selected for analysis. χ2 test and multivariate logistic regression were used for statistical analysis of the influencing factors of CVD and aggregation of CVD.ResultsThe proportion of high-risk CVD individuals in the population was 19.17%， including the high-risk individuals with hypertension （8.65%）， dyslipidemia （6.33%）， CVD history （5.58%）， and WHO assessed risk ≥20% types （2.69%）， respectively. Old age， overweight and obesity， central obesity， smoking， drinking， farmers， unmarried， and low family income were the risk factors of CVD， while high education level was the protective factor. In the participants， 16 323 people （81.34%） were classified as CVD high-risk groups； The number of aggregation of 1， 2 and ≥3 high risk types of CVD were 16 323（81.34%）， 3 236（16.13%）， 509（2.54%）， respectively. Old age， low education level， low annual family income， farmers， unmarried， smoking， drinking， overweight， obesity and central obesity were associated with the risk of aggregation of high risk types of CVD， and the correlation strength increased with the increase of aggregation types.ConclusionThe prevention and control of CVD in Shanghai should focus on the hypertension， elderly， overweight， obesity， central obesity， smoking， drinking， low educated， low family income， farmers and unmarried people， and targeted intervention measures should be taken to reduce the risk of CVD among residents.